Estimasi Simpanan Karbon Hutan Mangrove Menggunakan Citra (SAR) Synthetic Aperture Radar Sentinel -1 di Taman Hutan Raya Ngurah Rai,Bali - Pradipta Wedayana, Gede Dicky; Karang, I Wayan Gede Astawa; As-syakur, Abd Rahman (Journal of Marine Research and Technology; Vol 6 No 1 (2023): FEBRUARI 2023DO - 10.24843/JMRT.2023.v06.i01.p03, 2023)
Taman Hutan Raya (Tahura) Ngurah Rai, Bali, is recorded to have a mangrove forest covering an area of 1,373.5 ha, which plays a role in absorbing carbon from the atmosphere. Carbon is stored in the form of biomass. The bigger the biomass, the bigger the carbon stock in it. Direct measurement of biomass in the field requires an expensive method, a relatively long time, and narrow area coverage. Nowadays, the weakness of measuring carbon stocks directly in the field can be overcome by remote sensing approaches, especially estimations from satellite imagery combined with geographic information systems (SIG). One of the images that can be used to estimate carbon stock is the Sentinel-1 Synthetic Aperture Radar (SAR) image. The aim of this research is to estimate biomass and carbon stocks based on SAR backscatter distribution. The method used is the analysis of satellite imagery combined with field data. Field data collection and above-ground biomass (AGB) calculations were carried out by taking 30 plots with a plot size of 10 x 10 m. The results showed that there was a correlation between the backscatter value of SAR images and AGB from field measurements (r = 0.59 and the AGB estimation model y = 57.42x + 1223.8, where y is biomass and x is backscatter), and the coefficient of determination R2 = 0.36. The estimation model developed next is used to calculate the overall AGB, which is then used to estimate the overall aboveground carbon storage.